Association of eosinopenia with worsening prognosis in hospitalized Azvudine-treated COVID-19 patients: a retrospective cohort study - Wang, Xiaomin; Dian, Yating; Zhou, Qian; Deng, Guangtong; Wei, Rui; Zeng, Furong (Frontiers in Immunology, 2023)
Background: Current guidelines prioritized the use of Azvudine in Coronavirus Disease 2019 (COVID-19) patients, while biomarkers for prognosis in Azvudine-treated COVID-19 patients are still lacking. Here, we aim to assess the prognostic value of eosinopenia in Azvudine-treated COVID-19 patients. Methods: We retrospectively reviewed 290 consecutive Azvudine-treated hospitalized COVID-19 patients. Clinical characteristics and prognosis data were analyzed between patients with eosinopenia and with normal eosinophil levels. Results: A total of 290 patients were enrolled in this study, with a median age of 69 years. Among them, 40.69% patients presented with eosinopenia, and 59.31% patients were with normal eosinophil levels. Common symptoms included cough (87.6%), expectoration (76.2%), fever (67.9%), poor appetite (47.2%), and polypnea (46.6%). Compared to patients with normal eosinophil levels, those with eosinopenia were older and less likely to experience fatigue (25.4% vs 39.0%, P=0.016). Significant differences in laboratory parameters, particularly in blood routine and blood biochemical indicators, were observed between the two groups. Patients with eosinopenia were also less likely to develop severe illness subtypes, requiring more medications and oxygen support. Cox proportional hazard model showed that eosinopenia was associated with worsening progression in Azvudine-treated COVID-19 patients (adjusted hazard ratio=2.79, 95% confidence interval: 1.04, 7.50), adjusting for potential confounders. Conclusions: Eosinopenia is associated with worsening prognosis in Azvudine-treated COVID-19 patients.